Analisis Faktor-Faktor yang Mempengaruhi Kinerja Kepala Desa di Kabupaten Kuantan Singingi dan Kabupaten Kampar - Sonia Sischa Eka Putri; Pivit Septiary Chandra (Owner : Riset dan Jurnal Akuntansi, 2021)
This study aims to see the effect of clarity of budget targets, internal control systems, motivation and organizational commitment to the performance of village heads in Kuantan Singingi and Kampar districts. This research was conducted in 2020 to see the performance of the village head, this is because there are still problems related to the performance of the village head that the community complains about, therefore the authors want to measure whether the clarity of budget targets, internal control systems, motivation and organizational commitment have an effect on the performance of the village head. The type of data used is primary data by using questionnaire method of data collection.. The sample in this study were village heads totaling 60 people. The results of this study indicate that the clarity of budget targets has an influence on the performance of the village head, the internal control system has an influence on the performance of the village head, motivation and organizational commitment also has an influence on the performance of village heads in Kuantan Singingi and Kampar Districts. From all the testingist done it can be concluded that the variables of budget targets, internal control systems, motivation and organizational commitment that it used to explain 63% of villages head performance. While there meaning 37% are influence do rexplained by other variables not included in this study.